PERAN GURU TPQ BAITUL IBADAH DALAM MEMBINA AKHLAK ANAK DI DESA BRAJA INDAH - Novita Herawati (AS-SALAM, 2021)
Abstract This research is to find out the role of TPQ teachers in fostering children's morals, especially in Braja Indah village, Braja Selebah district, East Lampung. Morals are a measure of one's faith. To achieve moral perfection, coaching is needed. The coaching is not only carried out by formal and informal institutions, but also non-formal institutions in the community, namely TPQ. This is where the role of the teacher lies, one of which is in the Al-Qur'an Education Park. TPQ teachers are educators from non-formal educational institutions who teach the ability to read and write the Qur'an as well as teach knowledge about worship, faith, and morals. The method used is descriptive qualitative, with empirical data from observations and interviews. That the role of the TPQ teacher is as 1) the role of the TPQ teacher as a role model/model for children, 2) the teacher familiarizes children with good character, 3) the teacher as a supervisor and 4) the teacher as a child advisor. Keywords: The Role of TPQ Teachers, Children's Morals ABSTRAK Penelitian ini bertujuan untuk mengetahui peran guru TPQ dalam membina akhlak anak khususnya di desa Braja Indah Kecamatan Braja Selebah Lampung Timur. Akhlak menjadi tolak ukur keimanan seseorang. Untuk mencapai kesempurnaan akhlak, dibutuhkan adanya pembinaan. Dalam pembinaan tersebut tak hanya dilakukan oleh lembaga formal dan informal saja, melainkan juga lembaga non formal yang ada di lingkungan masyarakat, yakni TPQ. Disinilah letak peran guru salah satunya di Taman Pendidikan Al-Qur’an. Guru TPQ adalah tenaga pendidik dari lembaga pendidikan non formal yang mengajarkan kemampuan membaca dan menulis Al-Qur’an juga mengajarkan pengetahuan tentang ibadah, akidah, dan akhlak. Metode yang digunakan melalui kualitatif deskriptif, dengan data-data empiris observasi dan wawancara. Bahwa peran guru TPQ adalah sebagai 1) peran guru TPQ sebagai Tauladan contoh/model bagi anak, 2) Guru membiasakan anak berakhlakul karimah, 3) Guru sebagai pengawas dan 4) Guru sebagai penasehat anak. Kata Kunci: Peran Guru TPQ, Akhlak Anak